Methods for Assessing Factors Affecting the Efficiency of Small Businesses - Mavrulov Ravsha Nematjonovich (Goodwood Publishing, 2026)
Purpose: To analyze and evaluate methods for assessing factors that influence the efficiency and performance of small businesses, particularly in terms of resource utilization, productivity, and their contribution to regional economic development and employment. Research Methodology: This study applies a mixed-methods approach combining qualitative and quantitative analysis. Data were collected through structured questionnaires, semi-structured interviews, and secondary financial data from small enterprises. Analytical techniques included descriptive statistics, correlation analysis, multiple regression, and thematic qualitative analysis. Results: The results indicate that the efficiency of small businesses is influenced by several internal and external factors, including financial management practices, human resource productivity, operational processes, market orientation, and institutional conditions. The findings highlight that relying solely on financial indicators is insufficient, and a multidimensional assessment approach is necessary to evaluate performance effectively. Conclusions: The study concludes that evaluating small business efficiency requires an integrated framework that links resource productivity, operational efficiency, financial performance, and strategic outcomes. Such an approach enables better managerial decision-making and supports effective policy formulation for small business development. Limitations: The research is limited by the use of self-reported data and a cross-sectional design, which may restrict the ability to observe long-term causal relationships. Contributions: This study provides a comprehensive framework for assessing small business efficiency and offers practical insights for policymakers, entrepreneurs, and researchers in improving productivity, competitiveness, and sustainable economic growth.